Late-time cosmology without dark sector but with closed string massless sector - Hocheol Lee; Jeong-Hyuck Park; Liliana Velasco-Sevilla; Lu Yin (Physics Letters B)
We explore the possibility of solving the dark energy and the coincidence problems by postulating the massless sector of closed strings. This sector constitutes the gravitational multiplet of string theory and, when applied to four-dimensional cosmology, predicts that the expansion of an open Universe defined in string frame is readily accelerating. We confront the prediction with the late-time cosmological data of Type Ia supernovae and quasar absorption spectrum, which probe the evolutions of the Hubble parameter and possibly the fine-structure constant. We report that these observations are in admirable agreement with the prediction without any dark sector or coincidence problem. We estimate the Hubble constant, H0≃71.2±0.2km/s/Mpc.